Advanced glycation end product accumulation was associated with renal function impairment in males in large health examination population - Ryo Asaoka; Shigeki Muto; Akira Obana (PLoS ONE, 2026)
The accumulation of advanced glycation end products (AGEs) is a risk factor for renal dysfunction. However, no investigation has been conducted on the association between AGEs and renal function in health screening participants. Therefore, this study aimed to examine the association between AGEs and kidney function in health screening participants who underwent health screening examination. Overall, 1,651 health screening examinees without a history of renal dysfunction diagnosis were recruited and AGE accumulation was measured by skin autofluorescence (SAF). The association between estimated glomerular filtration rate (eGFR) and AGEs was subsequently investigated in all examinees. The mean age was 56.6 ± 9.5 years; 812 (49.1%) were males, and the mean eGFR was 73.3 ± 13.4 mL/min. Multiple regression analysis identified that AGEs were significantly negatively associated with eGFR. This finding was also observed in examinees with normal eGFR (≧ 90 mL/min/1.73 m 2 , G1 stage according to the Japanese Society of Nephrology: N = 207). In conclusion, skin AGEs were significantly negatively associated with eGFR. To clarify whether AGEs contribute to renal dysfunction progression, additional research is required.